Perbandingan Kadar IL-1α antara Tindakan Debridement Tajam Agresif dan Debridement Tajam Konservatif pada Penderita Kaki Diabetik - Tjiptadi, Vincent D.; Tangkilisan, Adrian (JURNAL BIOMEDIK : JBM, 2018)
Abstract: Diabetic foot is a chronic complication of diabetes mellitus which is commonly found but very threatening due to its unsatisfied management, usually ended with amputation or death. Sharp debridement is the gold standard of diabetic foot, albeit, it has to be considered wisely due to the metabolic disorder, sepsis, and other comorbid factors of the patients. This study was aimed to compare the dynamics of Il-1α levels in patients with aggresive sharp debridement and with conservative sharp debridement associated with clinical improvement. This was an experimental analytical study. There were 38 patients with diabetic foot admitted at Prof. Dr. R. D. Kandou Hospital Manado with an age range of 30-60 years, obtained by using simple random sampling. The patients were divided inti two groups: aggressive sharp debridement dan conservative sharp debridement, each of 19 patients. Samples for laboratory examination were collected before and after debridement. In consevative sharp debridement group, the mean levels of IL-1α before treatment was 108,158±14,519 pg/ml meanwhile after treatment was 108,526±16,625 pg/ml that showed no significant elevation. In aggressive sharp debridement group, the mean levels of IL-1α before treatment was 93,263±15,172 pg/ml meanwhile after treatment was 104,052±18,807 pg/ml that showed a significant elevation. Conclusion: In patients with diabetic foot, elevation of IL-α levels after aggressive sharp debridement was greater than after conservative sharp debridement.Keywords: diabetic foot, sharp debridement, interleukin 1-αAbstrak: Kaki diabetes merupakan salah satu komplikasi kronik diabetes melitus yang sering dijumpai dan ditakuti oleh karena pengelolaannya sering mengecewakan dan berakhir dengan amputasi, bahkan kematian. Penanganan dengan debridemen tajam pada pasien dengan kaki diabetik merupakan baku emas tetapi masih dipertimbangkan akibat adanya gangguan metabolik, sepsis dan faktor komorbid lainnya. Penelitian ini bertujuan untuk menganalisis tindakan debridement tajam agresif dan konservatif pada pasien kaki diabetik dengan dinamika kadar IL-1α dan hasil perbaikan klinis. Jenis penelitian ialah eksperimental analitik. Populasi penelitian ialah pasien kaki diabetik yang dirawat di RSUP Prof. Dr. R. D. Kandou Manado dengan rentang usia 30-60 tahun. Subjek penelitian diperoleh dengan simple random sampling, terdiri dari 38 pasien, dibagi atas dua kelompok: tindakan debridemen tajam agresif dan debridemen tajam konservatif, masing-masing 19 pasien. Pengumpulan sampel untuk pemeriksaan laboratorik dilakukan sebelum dan setelah masing-masing tindakan. Pada kelompok tindakan konservatif didapatkan rerata nilai IL-1α sebelum tindakan ialah 108,158±14,519 pg/ml sedangkan setelah tindakan ialah 108,526±16,625 pg/ml yang menunjukkan tidak terdapat peningkatan bermakna. Pada kelompok tindakan agresif nilai IL-1α sebelum tindakan ialah 93,263±15,172 pg/ml sedangkan setelah tindakan ialah 104,052±18,807 pg/ml yang menandakan peningkatan bermakna. Simpulan: Peningkatan kadar IL-α setelah tindakan debrideman tajam agresif lebih besar dibandingkan setelah tindakan debrideman tajam konservatif pada penderita kaki diabetik.Kata kunci: kaki diabetik, debridemen tajam, interleukin 1-α